2016
DOI: 10.1007/s11845-016-1414-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin versus insulin in gestational diabetes mellitus: a meta-analysis of randomized clinical trials

Abstract: Metformin may be beneficial in treating gestational diabetes. However, even more studies are needed to provide more evidence for the future use of metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…This necessitates careful dosage adjustment as pregnancy progresses. There is a risk of metformin accumulation in the neonate prior to birth, through recycling of amniotic fluid …”
Section: Metformin In Pregnancy: Translation Of Pharmacology To Practicementioning
confidence: 99%
“…This necessitates careful dosage adjustment as pregnancy progresses. There is a risk of metformin accumulation in the neonate prior to birth, through recycling of amniotic fluid …”
Section: Metformin In Pregnancy: Translation Of Pharmacology To Practicementioning
confidence: 99%
“…[13][14][15][16][17][18][19] Several studies have shown fewer BMI changes among obese women with GDM treated with this drug. [20][21][22] The results of the present study identified that participants in both control and metformin groups showed no significant increase in BMI between gestational weeks 20 and 24-28. The combination of metformin with lifestyle changes represents a potentially effective and safe approach to obesity control.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, treatment of GDM with metformin has recently increased in Norway, Wales, and the rest of the UK [50]. Evidence from randomized controlled trials and observational studies revealing no adverse maternal or fetal/neonatal effects in the short-term [51, 52] supports using metformin for GDM [18]. The 2013 MiG trial comparing insulin vs. metformin for treating gestational diabetics confirmed the safety of metformin in pregnancy and revealed no differences in either maternal circulating hormones/metabolites, birth weight, or neonatal anthropometric measurements between the two treatments [53].…”
Section: Discussionmentioning
confidence: 99%